2010
DOI: 10.1371/journal.pone.0011339
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Symbionts in Insects Influence Down-Regulation of Defense Genes in Maize

Abstract: Diabrotica virgifera virgifera larvae are root-feeding insects and significant pests to maize in North America and Europe. Little is known regarding how plants respond to insect attack of roots, thus complicating the selection for plant defense targets. Diabrotica virgifera virgifera is the most successful species in its genus and is the only Diabrotica beetle harboring an almost species-wide Wolbachia infection. Diabrotica virgifera virgifera are infected with Wolbachia and the typical gut flora found in soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
113
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(117 citation statements)
references
References 48 publications
3
113
0
Order By: Relevance
“…As this sequence of events is specifically triggered by disruption of the symbiosis rather than anthelminthic chemotherapy per se, wOo could be considered a defensive mutualist. This phenotype is now well recognized for Wolbachia in arthropods, and a precedent involving manipulation of the immune system of a third party exists for an insect pest of maize (Barr et al 2010). Moreover, in L. sigmodontis, successful migration of the infective larvae is also associated with immunomodulation of mammalian effector cells by Wolbachia (Specht et al 2011).…”
Section: Discussionmentioning
confidence: 96%
“…As this sequence of events is specifically triggered by disruption of the symbiosis rather than anthelminthic chemotherapy per se, wOo could be considered a defensive mutualist. This phenotype is now well recognized for Wolbachia in arthropods, and a precedent involving manipulation of the immune system of a third party exists for an insect pest of maize (Barr et al 2010). Moreover, in L. sigmodontis, successful migration of the infective larvae is also associated with immunomodulation of mammalian effector cells by Wolbachia (Specht et al 2011).…”
Section: Discussionmentioning
confidence: 96%
“…In maize roots, larvae of the western corn rootworm (D. virgifera virgifera) inhibited the induction of defense gene expression, which was not observed when insects were treated with the antibiotic tetracycline (13). The authors reported that larvae with Wolbachia infection suppressed plant-defense-related gene transcripts, although the effect of suppression on insect performance was not examined.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, symbionts can influence plant-insect interactions (12,13). Symbiotic bacteria may allow some herbivores to expand the range of available host plants.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies in the western corn rootworm ( Diabrotica virgifera virgifera ) and the tomato psyllid ( Bactericera cockerelli ) have found higher concentrations of endosymbionts correlate with reduced expression of plant defensive pathways (Barr et al. 2010; Casteel et al. 2012).…”
Section: Discussionmentioning
confidence: 99%